Magnetotelluric studies in the epicenter zone of 2001, Bhuj earthquake. (February 2015) - Mohan, Kapil; Rastogi, B.K.; Chaudhary, Peush
Abstract: Some earthquakes to Mw5 level are occurring along two faults viz. Kachchh Mainland Fault and South Wagad Fault near the epicenter of Mw7.7 Bhuj earthquake of 2001. These faults are not the causative fault of the 2001 earthquake and suspect for future large earthquake. In absence of detail geophysical surveys, the sub-surface orientation of these faults was not known and MT profiles have proved useful in delineating the subsurface trends. Two MT profiles having lengths of 24 km and 15 km (with an inter station spacing of 1–3 km) are taken about 10 km east and west of the epicenter of Mw7.7, 2001 Bhuj earthquake, respectively. The profiles are in nearly N–S direction to detect the faults which trend E–W in the area. From 2-D inversion of MT data of 23 stations, it is found that there are two distinctive conductive features matching with the South Wagad Fault and Kachchh Mainland Fault south of it both being about 10 km apart. The South Wagad Fault is seen extending to Banni low lying area 30 km west of the present trace.